Management Accounting of Transaction Cost of Enterprises of Oil and Gas Complex - Коцкулич, Т. Я. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
The legislative basis of transaction costs accounting, possible ways of accounting organization which were revealed in works of domestic and foreign scientists were investigated in the article, their strong and weak sides were characterized. The model of managerial accounting of transaction costs which does not conflict with demands of valid legislative was worked out. The key peculiarities of the oil and gas industry enterprises which could effect on transaction costs accounting were described.